LOCAL VALUE-BASED PERFORMANCE MEASUREMENT SYSTEM IN COFFEE CULTIVATION: A BEHAVIORAL STUDY IN COFFEE PLANTATION COMMUNITIES IN SUBANG - Apriliani, Anissa; Iskandar, Riska Aditya Putri (JABI (Journal of Accounting and Business Issues), 2026)
This study aims to design and analyze a performance measurement system based on local values in coffee cultivation within farmer communities in Subang, Indonesia. A qualitative approach was employed through in-depth interviews, focus group discussions, and participatory observations to explore farmers’ perceptions, community leaders’ roles, and related stakeholders’ perspectives on integrating local values into agricultural practices. The findings reveal that local values such as mutual cooperation, environmental conservation, the use of organic fertilizers, and the inheritance of traditional farming practices significantly influence farmers’ behavior in implementing sustainable agricultural methods. The farmer community has developed an informal performance measurement system that goes beyond yield quantity, incorporating social, ecological, and cultural dimensions. This local value–based system offers a more holistic and fair approach compared to conventional models, supporting agricultural sustainability, strengthening social solidarity, and increasing the economic value of coffee products. These findings are expected to serve as a basis for policy development and performance evaluation models that are relevantto local cultural characteristics.